Peran Transforming Growth Factor? terhadap Tingkat Kematangan dan Kejadian Apoptosis Oosit Sapi pada kultur In Vitro - -, Widjiati; -, Rimayanti; boediono, Arief; Setiadi, Agus (Jurnal Veteriner; Vol 11 No 2 (2010))
Low productivity of in vitro embryo production at blastosis level appears to be as a result of imperfectoocyte maturation which causes imperfect oocyte growth, and in turn will affect the embryo growth. Inaddition to hormonal factor, growth factor plays significant role in maturation process of oocytes. Asgrowth factor might has a significant role during maturation process, a study was conducted to determinewhether transforming growth factor ? (TGF ?) isolated from oocytes of cumulus complex is required for coculture and in vitro embryo production.. Oocytes were collected from follicles with the diameter of 3-5 mmand > 5 mm. Then the oocytes were cultured for 22 hours at 38.5o with 5% CO2 atmosphere in tissueculture medium (TCM) 199 supplemented with 5 ?g/mg luteonizing hormone (LH), 3% bovine serumalbumin (BSA) 50 ?g/ml gentamycin sulfat and three different levels of TGF ? (12,85 pg/ml, 25,7 pg/mland 38,55 pg/ml). The oocyte maturation and number of apoptosis cells were examined. The result showedthat oocyte maturation in medium supplemented TGF ? at the dose of 38,55 pg/ml was better than in thatat dose of 12,85pg/ml or 25,7 pg/ml. The best maturation was observed at metaphase II stage of oocytedevelopment. No apoptosis was observed during maturation of oocytes. Supplementation of TGF ? at thedose of 38,55 pg/ml in culture medium increased the oocyte maturation without causing a significantapoptosis in vitro.
Keywords: TGF ?, apoptosis, cumulus complex